Quality Improvement through Mechanization of Tail Gate Weather Strip Assembly Process - Suresh, R; Palani, R; Rajamanickam, S; Arumugam, K; Sathiyamoorthy, V; Logeshwaran, D (International Journal of Engineering and Technology, 2018)
The Assembly plant #1 at Hyundai Motors India Limited consists of assembly line A1, A2 and A3. In these, assembly line A1 and A2 are semi-automatic in manner where at some stations manual assembly is involved. Cycle time should be considered a viable option when an organization is trying to improve efficiency and productivity and hence this paper deals with the reduction of fatigueness as well as cycle time in station #190 of ASY#1 where tailgate weather-strip is fixed manually. The Journal undertaken was to design work assist system (standalone device) which is used to position tailgate weather strip for GS Model (Hyundai Creta). For this many activities were done and analyzed the problem and designed the work assistor seeing through all the constraints. Thus the entire machine assembly will be done to minimize the operator fatigue, to improve quality and also the chances of disorientation are reduced by elimination of manual hand operation. Fatigue reduction was shown by calculating the difference of frictional force between hand and the standalone device and the frictional force was reduced by 4.91N.The shower results bettered with less rejection by using the operator-friendly work assist system.Â Â